Biomass-derived porous carbon supported CoCoO yolk-shell nanoparticles as enhanced multifunctional electrocatalysts. (8th March 2019) - Yang, Mengjie; Wu, Dengfeng; Cheng, Daojian
Abstract: Developing highly efficient, durable and low-cost electrocatalysts for oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in energy conversion and storage is still required, urgent and challenging. Herein, a novel structure of biomass-derived nitrogen-doped porous carbon supported yolk-shell CoCoO nanoparticles (yolk-shell CoCoO/BC) was successfully prepared via a facile impregnation strategy. The pyrolysis temperature and heating rate of Co 2+ /BC composite are two key factors in the formation of the yolk-shell structure. The synthesized yolk-shell CoCoO/BC exhibits excellent electrochemical activity and stability as multifunctional electrocatalysts. The yolk-shell CoCoO/C with a positive onset potential (0.91 V vs. RHE) and half-wave potential (0.82 V vs. RHE) exhibits an effective 4-electron transfer path and excellent methanol tolerance in alkaline electrolyte for ORR. Moreover, a low cell potential ( η 10  = 1.77 V vs. RHE at the current density of 10 mA cm −2 ) for overall water splitting can be reached. The synergistic catalytic effects between BC support and yolk-shell CoCoO nanoparticles should be responsible for the excellent performance for ORR, OER and HER. This work opens up a way to the facile fabrication of carbon supported yolk-shell nanostructures with high-performance in electrocatalytic applications for ORR, OER and HER. Highlights: Yolk-shell CoCoO/BC was prepared via a facile impregnation strategy. Heating temperature and rate are vital to the formation of yolk-shell structure. Yolk-shell CoCoO/BC shows excellent catalytic performances for ORR, OER and HER.